Enhanced production of Rauscher leukemia virus after infection of high-passaged JLS-V9 cells. - Perry, A (1978)
JLS-V9, a mouse bone marrow cell line infected with Rauscher leukemia virus at high passage level, produced larger amounts of virus than the standard JLS-V10 cells. The enhanced virus production was attributed to the increased saturation density of JLS-V9 cells.